LIQUIDITY AND SOLVABILITY ON PROFITABILITY: A STUDY ON TELECOMMUNICATION COMPANIES LISTED AT INDONESIAN STOCK EXCHANGE FROM YEAR 2014-2018 - Francis Hutabarat (Jurnal Ilmu Akuntansi, 2020)
It is the purpose of every company to get the maximal profit and continuing its company’s life by maintaining and expanding the company. This research is conducted to know the influence of liquidity and solvability on to profitability of the company of telecommunication companies listed in the Indonesia Stock Exchange from 2014 to 2018. Data used from financial statements in the Indonesian Stock Exchange. The independent variable from this research is liquidity and solvability and the dependent variable in the study is profitability. This research used multiple regression linear technique analysis. The research target is to: knowing what liquidity has an effect on to profitability by partial and solvability have an effect on profitability by partial.